Conservation priorities for elementary school students: Neotropical and European perspectives - Rosalino, L. M.; Gheler-Costa, C.; Santos, G.; Gonçalves, M. T.; Fonseca, C.; Leal, A. I. (Biodiversity and Conservation, 2017)
Nature conservation can only be an efficient process if involving different society actors, especially those that have long-term and multiplying effects on how society relates with nature, such as children/students. To delineate nature conservation strategies, we need to understand the drivers that shape peoples’ behaviors and attitudes towards nature; for students this is mostly determined by their past experience and influence of their socio-economic and familiar context. To test these assumptions, we develop a study focused on elementary school students from Portugal and Brazil. In each country we selected two student’s groups representing two distinct socio-environmental contexts: rural and urban populations. Based on a written questionnaire, we aimed at understanding the effect of parental and socio-environmental contexts, gender, prior contact with nature and online news-associated environmental information, on how students prioritize taxa to be conserved. Furthermore, we analyzed how health, economic and touristic values constrain pro-conservation attitudes. Students from urban areas and from Portugal showed a lower probability of having a pro-conservation attitude. Brazilian and rural students may have a more frequent contact with nature and live in regions of higher biodiversity, two factors that may act synergistically to produce those patterns. Positive attitudes towards conservation seem to be over-ruled by health (i.e. self-preservation) and economical (i.e. financial subsistence) interests and values. Moreover, students prioritize for conservation species that are commonly mentioned in the online news, particularly mammals, and plants. Acknowledging that students rank higher health and economical values over conservation ones, as well as the perceptible importance of contacting with nature and the apparent relevance of online news as information vehicles, may increase the chances of improving the efficacy of nature conservation strategies. Furthermore, this information can lead to an improvement of environmental awareness and literacy.